Effect of nutrients level and source on feed intake, nutrients digestibility, rumen profile, blood metabolites and growth in Bhadawari buffalo female calves - SINGH, SULTAN; KUSHWAHA, B P; MAITY, S B; SINGH, K K; DAS, N (The Indian Journal of Animal Sciences, 2014)
In a nutritional experiment 15 Bhadawari female calves (77.47±6.92 kg; 11.0 months age) divided equally into 3 dietary groups (G1, G2 and G3) were fed wheat straw- berseem- concentrate mixture (CM) based diets to evaluate the response of dietary protein and energy concentrations on intake, nutrients digestibility, rumen metabolites and growth. Calves in G1 were offered were offered wheat straw, berseem and concentrate mixture to meet protein and energy requirements (ICAR 1985), while in G2 and G3 calves were given 25% less nutrients than G1. In G2 50% of CM was replaced with green berseem, while in G3 100% of CM was replaced with berseem and given 500 g maize grain as energy source. In G1, G2 and G3 protein was met through CM: berseem (75: 25), CM: berseem (50: 50) and berseem (100%), respectively. DMI (g/kg w 0.75) was 86.97, 77.47 and 79.18 in G1, G2 and G3, respectively. DM, CP, NDF, ADF and cellulose digestibility of calves on different diets was similar. Nitrogen metabolites concentration in rumen liquor of calves was higher in G1 than G2 and G3, while TVFA concentration was 100.0, 110.0 and 90.0 meq/l in G1, G2 and G3, respectively. Total protozoa counts were comparable, while sporangia counts in rumen liquor of buffalo calves were higher in G1 than G3. Blood glucose, protein and urea were similar in calves of all the groups. Calves growth rate was higher in G1 than G2 and G3. Dietary DCP and ME contents were similar, while feed and nutrients conversion ratio for body weight gain was relatively lower for G1 than other dietary groups. Study showed that there was no significant effect of levels and sources of nutrients from the present diets on calves’ intake, nutrients digestibility and growth rate, however rumen liquor N contents and, sporangia counts - were higher in G1 than G2 and G3 groups.